PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DIREKTORAT PRODUKSI PT DIRGANTARA INDONESIA (PERSERO) - Prasetyo, Agung Budi; Suhaeni, Tintin (Jurnal Riset Bisnis dan Investasi, 2015)
PT Dirgantara Indonesia (Persero) is a manufacture company that provides airplane with component and service. The company has 4.225 employees. Organization culture is one of important thing that have to attentively by a company because this one possible to affect for employee performance. This research aims to determine organization culture and employee performance and the influence of organization culture on employee performance at Production Directorate PT DI. Organizational culture can be seen from the lack of implementation of the company value while the performance can be seen from the production does not reach the target and the grade of the employee's performance is still low. The method which is used in this research is quantitative research methods. Data analysis method which is used in this research are descriptive analysis, a classic assumption test, correlation analysis, regression analysis, and hypothesis testing. The sample in this research 107 respondents. The data collection is used questionnaire with Likert scale. Based on the results of data processing, organization culture currently on good category, it can be seen from innovation and risk taking, attention to detail, outcome orientation, people orientation, team orientation, aggresiveness, and stability. Then, employee performance also currently on good category, it can be seen from quantity the of work, quality of work, knowledge of job, personal qualities, cooperation, dependability, and initiative. The conclusion of this research is there’s an influence of organization culture on employee performance amounted to 28,2% which have positive by value amount 0,531 which means medium and significant value.